In vitro anthelmintic activity of neem leaves (Azadirachta indica ) chloroform extract against the third-stage larvae of strongyles from sheep - Suhaimi, Nurul Hairunnisa (2016)
Parasitic disease causes mortality and morbidity of sheep in Malaysia. Neem plant (Azadirachta indica) has been shown to possess medicinal values such as anti-fungal, antibacterial, anti-inflammatory and anthelmintic activity. This study was conducted to determine the in vitro anthelmintic effect of neem leaves on the third-stage larvae (L3) of strongyles from sheep. Pooled faecal samples from 22 sheep with the history of gastrointestinal parasitism were cultured to harvest the L3. Three thousands L3 were divided into five groups of six petri dishes each containing one hundred L3 per dish. Three groups were tested with the neem leaves (Azadirachta indica) chloroform extract (ACE) at 5, 10 and 15mg/ml concentrations, one positive control group (levamisole, 10 mg/ml) and one negative (0.01% DMSO + deionized water). The L3 mortality was observed for 2, 4, 6, and 24 hours. Results showed that the percentage L3 mortality were 93% (ACE 5 mg/ml of 24 hours post-treatment) and 83% (ACE 10 mg/ml 2 hours post-treatment). All ACE treated groups showed significant anthelmintic efficacy against L3 compared to the negative control group (KW=93.55, df=4, p<0.05). Further studies related to the effect of using lower ACE concentrations on L3 mortality of strongyles from sheep are suggested.